Why diachronicity matters in the study of linguistic landscapes - Pavlenko, Aneta; Mullen, Alex (John Benjamins Publishing, 2015)
It is commonly argued that the proliferation of urban writing known as linguistic landscapes represents “a thoroughly contemporary global trend” (Coupland, 2010: 78). The purpose of this paper is to show that linguistic landscapes are by no means modern phenomena and to draw on our shared interest in multilingual empires to highlight the importance of diachronic inquiry and productive dialog between sociolinguists of modern and ancient societies. We will argue that while signs do operate in aggregate, the common focus on all signs at a single point in time on one street is problematic because the interpretation of signs is diachronic in nature, intrinsically linked to the preceding signs in the same environment and to related signs elsewhere, and the process of reading “back from signs to practices to people” (Blommaert, 2013: 51) is not as unproblematic as it is sometimes made to look.